‘I ALMOST CRIED’: PRE-SERVICE TEACHER’S EMOTIONAL EXPERIENCES DURING A TEACHING PRACTICUM - Purwanto, Luthfia Navaberliana; Fitriyah, Siti Masrifatul; Ariani, Musli (ELLTER Journal, 2024)
Emotions are closely related to teaching and learning activities, especially for pre-service teachers as beginners in the field of teaching. In the classroom, there is not only an exchange of knowledge but also effective aspects of teaching and learning that might be challenging for pre-service teachers as they are mostly unfamiliar with the real classroom situation. Thus, this study aimed to explore and investigate one of the authors’ as a pre-service teacher's emotional experiences during a teaching practicum program, chosen through a purposeful sampling technique. The selected participant met the requirements for the study: an EFL pre-service teacher assigned to a teaching practicum program, capable and willing to write diary entries for data collection. To record the emotional experiences, the participant wrote diary entries during practicum. The data collection will be analyzed using categorical content analysis before writing the findings in narrative form. The findings explicate that pre-service teacher experienced both negative and positive emotions as a result of their interaction related to academic activities and their environment. Both emotions were found to affect pre-service teacher’s strategy, motivation, creativity, goals, students’ learning outcomes, and the whole teaching practicum experience.